The Holy in Hindu culture : it's veiling an unveiling - Weber, Edmund (Journal of religious culture, 2025)
As in most religious cultures, Hinduism also engages in a spiritual struggle between veiling and unveiling the Holy. This is classified in terms of the dialectical theory of religion using selected texts from the Rigveda, the Bhagavata Purana, the Vishnu Purana, the Institutes of Vishnu, the Vedanta Sutras of Badarayana, the Eight Verses of Shri Krishna Caitanya, and the Tiruvasagam of Manikkavasagar.